Stroke-Induced Modulation of Myeloid-Derived Suppressor Cells (MDSCs) and IL-10-Producing Regulatory Monocytes - Achmus, Lennart; Ruhnau, Johanna; Grothe, Sascha; von Sarnowski, Bettina; Bröker, Barbara M.; Dressel, Alexander; Schulze, Juliane; Vogelgesang, Antje (Frontiers in Neurology, 2020)
Abstract Background: Stroke patients are at risk to acquire secondary infections due to stroke-induced immune suppression (SIIS). Immunosuppressive phagocytes comprise myeloid-derived suppressor cells (MDSC) and immunosuppressive IL10-producing monocytes. MDSC represent a small but heterogeneous population of monocytic, polymorphonuclear (or granulocytic) and early progenitor cells ("early" MDSC), which can expand extensively in pathophysiological conditions. MDSCs have been shown to exert strong immune suppressive effects. The role of IL10-producing immunosuppressive monocytes after stroke has not been investigated, but monocytes are impaired in oxidative burst and downregulate HLA-DR on the cell surface. Objectives: To investigate the regulation and function of MDSC as well as immunosuppressive IL10-producing monocytes in experimental and human stroke. Methods: This longitudinal monocentric non-interventional prospective explorative study used multicolor flow cytometry to identify MDSC subpopulations and IL-10 expression in monocytes in the peripheral blood of 19 healthy controls and of 27 patients on days 1, 3 and 5 post stroke. Quantification of intracellular STAT3p and Arginase-1 by geometric mean fluorescence intensity was used to assess functionality of MDSC. In experimental stroke monocytic (CD11b + Ly6G-Ly6C high) and polymorphonuclear MDSCs (CD11b + Ly6G + Ly6Clow) in spleen were analyzed by flow cytometry. Results: Stroke patients showed a relative increase in monocytic MDSC (percentage of CD11b+ cells) in whole blood without evidence for an altered function. The other MDSC subgroups did not differ from the control. Also, in experimental stroke, monocytic and in addition polymorphonuclear MDSC were increased. Numbers of IL-10 positive monocytes did not differ between patients and controls. However, we provide a new insight into monocytic function post stroke since we can report that a differential regulation of HLA-DR and PD-L1 was found depending on the IL-10 production of monocytes. IL-10 positive monocytes are more activated post stroke as indicated by their increased HLA-DR expression. Conclusions: MDSC and IL-10+ monocytes can induce immunosuppression within days after stroke.